Correlations among fatigue, respiratory function, balance and core muscle morphology in multiple sclerosis: a comprehensive observational study - Marta De La Plaza San Frutos; Ismael Sanz-Esteban; Ismael Sanz-Esteban; Federico Salniccia; Federico Salniccia; Alberto Bermejo-Franco; Alberto Bermejo-Franco; Ameyalli García-Corona; María Cristina Palma-Baquedano; Marina Castel-Sánchez; Marina Castel-Sánchez; Cecilia Estrada-Barranco; et al. (Frontiers in Neurology)
BackgroundRecent scientific interest has focused on exploring the potential relationships between fatigue, respiratory function and balance in multiple sclerosis (MS) subjects. While some studies suggest that fatigue may impact respiratory function and postural stability, the exact nature of these associations remains under investigation. Ultrasound imaging is increasingly being used to examine the structural and functional characteristics of core muscles, aiming to better understand how these variables might be interconnected. Understanding these associations is crucial for developing targeted interventions to enhance overall physical performance in this population. This study examines the relationship between fatigue, respiratory function, balance, and ultrasound variables of abdominal musculature in MS.MethodsA cross-sectional study was conducted involving 27 subjects diagnosed with MS, comprising 17 females and 10 males. Study variables were: fatigue (Modified Fatigue Impact Scale—MFIS); respiratory function (Forced Vital Capacity—FVC and Forced Expiratory Volume in the first second—FEV1); balance (Berg Balance Scale—BBS and Trunk Impairment Scale Dynamic—TIS DYN); and ultrasound measurements of abdominal and diaphragmatic musculature. Correlations were analyzed using Spearman’s correlation, with a statistical significance level of p < 0.05.ResultsSignificant correlations were found between respiratory function and balance scores. FVC showed a moderate correlation with BBS (r = 0.443), while FEV1 had a high correlation with BBS (r = 0.500) and a moderate correlation with TIS DYN (r = 0.427). MFIS showed a moderate negative correlation with BBS (r = −0.402). The strength and function of the central abdominal musculature, particularly the internal oblique, were crucial for trunk stability and postural control.ConclusionThese findings highlight the interplay between respiratory function, balance, fatigue, and abdominal muscle morphology in MS, emphasizing the potential benefits of interventions targeting respiratory function to improve balance and reduce fatigue, ultimately enhancing quality of life in this population.